Cultivating Ethical Leadership in Public Administration: Integrating Social Justice and Equity into Educational Programs in Sulu, Philippines - Datu Ansaruddin K. Kiram; Mharcelyn M. Kiram; Jul-Asri A. Hadjibun; Merhana Taraji (Enigma in Education, 2024)
Ethical leadership is crucial in public administration, particularly in regions like Sulu, Philippines, which faces complex governance challenges, including poverty, inequality, and conflict. This study explores the integration of social justice and equity into public administration educational programs to cultivate ethical leaders who can address these challenges effectively. A mixed-methods approach was employed, including a survey of 100 public administration students and faculty members in Sulu, and in-depth interviews with 10 experienced public administrators. Quantitative data were analyzed using descriptive statistics and correlation analysis, while qualitative data were analyzed1 thematically. The findings revealed a strong awareness among students and faculty of the importance of social justice and equity in public administration. However, there were gaps in integrating these concepts into the curriculum and pedagogy. Experienced administrators emphasized the need for practical experience and mentorship to develop ethical leadership skills in the context of Sulu's unique challenges. In conclusion, this study highlights the need for educational reform in public administration programs in Sulu to strengthen the cultivation of ethical leadership. Recommendations include incorporating experiential learning opportunities, community engagement, and culturally relevant case studies to bridge the gap between theory and practice.